Aflatoxin biosynthesis, genetic regulation, toxicity, and control strategies: a review - Khan, Rahim; Mohamad Ghazali, Farinazleen; Mahyudin, Nor Ainy; Samsudin, Nik Iskandar Putra (Multidisciplinary Digital Publishing Institute, 2021)
Aflatoxins (AFs) are highly toxic and cancer-causing compounds, predominantly synthesized by the Aspergillus species. AFs biosynthesis is a lengthy process that requires as minimum as 30 genes grouped inside 75 kilobytes (kB) of gene clusters, which are regulated by specific transcription factors, including aflR, aflS, and some general transcription factors. This paper summarizes the status of research on characterizing structural and regulatory genes associated with AF production and their roles in aflatoxigenic fungi, particularly Aspergillus flavus and A. parasiticus, and enhances the current understanding of AFs that adversely affect humans and animals with a great emphasis on toxicity and preventive methods.